Correlating laser‐generated melts with impact‐generated melts: An integrated thermodynamic‐petrologic approach. Issue 20 (28th October 2016) - Hamann, Christopher; Luther, Robert; Ebert, Matthias; Hecht, Lutz; Deutsch, Alex; Wünnemann, Kai; Schäffer, Sebastian; Osterholz, Jens; Lexow, Bernd
Abstract: Planetary collisions in the solar system typically induce melting and vaporization of the impactor and a certain volume of the target. To study the dynamics of quasi‐instantaneous melting and subsequent quenching under postshock P‐T conditions of impact melting, we used continuous‐wave laser irradiation to melt and vaporize sandstone, iron meteorite, and basalt. Using high‐speed imaging, temperature measurements, and petrologic investigations of the irradiation targets, we show that laser‐generated melts exhibit typical characteristics of impact melts (particularly ballistic ejecta). We then calculate the entropy gains of the laser‐generated melts and compare them with the entropy gains associated with the thermodynamic states produced in hypervelocity impacts at various velocities. In conclusion, our experiments extend currently attainable postshock temperatures in impact experiments to ranges commensurate with impacts in the velocity range of 4–20 km s –1 and allow to study timescales and magnitudes of petrogenetic processes in impact melts. Key Points: Laser melting of planetary materials forms melts with thermodynamic properties of impact melts originating from adiabatic decompression Laser‐generated melts are petrologically similar to impact melts and allow for estimating time scales of impact melt formation and cooling Direct laser irradiation of planetary materials simulates effectively the formation of impact melts and vapors in the 4–20 km s –1 range